Spin-Orbit Effect on Thermal Properties of Half-Heusler Alloy FeVSb: Anugrah Azhar - Anugrah Azhar Anugrah Azhar (Jurnal Fisika dan Aplikasinya, 2021)
FeVSb, a family of Half-Heusler alloy, is categorized as an n-type semiconductor which has a high figure of merit that makes this material to be one of the promising candidates for a thermoelectric device. In FeVSb, Fe and V atoms which have d-orbitals can be considered to have spin-orbit interaction that can affect the electronic structure and thermal properties of this material. In order to investigate how strong the spin-orbit interaction affect this material, we do the first-principles study by implementing the spin-orbit interaction to investigate the change of the band structure and thermal properties of FeVSb. Our results show that the spin-orbit interaction affects the band structure of the material indicated by the energy splitting in the electronic structure which increase the Seebeck coefficient, electrical conductivity, and thermal conductivity but slightly reduce the figure of merit values of FeVSb.